2018
DOI: 10.1016/j.conb.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite morphogenesis from birth to adulthood

Abstract: Dendrites are the conduits for receiving (and in some cases transmitting) neural signals; their ability to do these jobs is a direct result of their morphology. Developmental patterning mechanisms are critical to ensuring concordance between dendritic form and function. This article reviews recent studies in vertebrate retina and brain that elucidate key strategies for dendrite functional maturation. Specific cellular and molecular signals control the initiation and elaboration of dendritic arbors, and facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…Transcription factors act as intrinsic determinants of dendrite shape, in part by controlling the expression of cell-membrane proteins relevant for sensing extrinsic cues (Puram and Bonni, 2013;Dong et al, 2015;Lefebvre et al, 2015;Prigge and Kay, 2018). The discovery of transcriptionally different groups of T4/T5 neurons that match morphologically distinct T4/T5 subtypes during dendrite growth allowed us to search for candidate genes controlling subtype-specific dendrite orientations.…”
Section: Analysis Of Gene Expression Patterns Reveals Combinatorial Cmentioning
confidence: 99%
“…Transcription factors act as intrinsic determinants of dendrite shape, in part by controlling the expression of cell-membrane proteins relevant for sensing extrinsic cues (Puram and Bonni, 2013;Dong et al, 2015;Lefebvre et al, 2015;Prigge and Kay, 2018). The discovery of transcriptionally different groups of T4/T5 neurons that match morphologically distinct T4/T5 subtypes during dendrite growth allowed us to search for candidate genes controlling subtype-specific dendrite orientations.…”
Section: Analysis Of Gene Expression Patterns Reveals Combinatorial Cmentioning
confidence: 99%
“…In some cells, dendrite growth and remodeling continue into adulthood (Prigge & Kay, 2018). Neuronal activity is important for the elaboration and stabilization of dendrite branches (Prigge & Kay, 2018). Therefore, it is necessary to determine the excitatory changes in individual hippocampal neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Along with axonal growth, proper establishment of neural circuitry firstly depends on the development of dendritic arborization. Extracellular cues cover an essential function in this process [ 26 ] and, interestingly, disturbing SEMAs expression results in aberrant dendritic development [ 27 , 28 ]. In vitro experiments showed that SEMA3A confers polarization to excitatory neurons [ 29 ], with dual effect as suppressor and promoter on axons and dendrites, respectively [ 30 ].…”
Section: Neuronal Maturationmentioning
confidence: 99%